The Effectiveness of Interactive Learning Media in Improving Students' Understanding of the Food Chain Concept in Elementary Schools - Mulyono; St. Y Slamet; Chumdari (Jurnal Penelitian Pendidikan IPA, 2025)
The inadequate comprehension of primary school pupils about the food chain concept is a significant issue in science education, exacerbated by traditional learning tools with limited interactivity. This research seeks to analyze the effectiveness of interactive learning media in enhancing primary school pupils’ comprehension of the food chain concept. The material was designed to suit primary school pupils’ cognitive development and aligns with the Independent Curriculum, which emphasizes active, contextual, and technology-supported learning. A quantitative approach was used with a quasi-experimental pretest-posttest control group design. Fifth-grade students from public elementary schools in Wonogiri Regency participated as subjects. Data was collected through a 25-item multiple-choice test. Analysis included normality and homogeneity tests, hypothesis testing using an independent sample t-test, and effect size calculation. Results showed a significant difference between experimental and control groups, with a significant value of 0.049 (<0.05), indicating the effectiveness of the media. The effect size of 0.530 classified the impact as high. In conclusion, interactive learning media significantly improves students’ comprehension by offering engaging and accessible learning experiences. These findings underscore the importance of integrating technology into science education to enhance learning outcomes and support student-centered approaches.